ADS404 - Introduction to Public Administration / Faculty of Administrative Science & Policy Studies - UiTM, Faculty of Administrative Science & Policy Studies (Universiti Teknologi MARA (UiTM), 2023)
The course will provide an overview of the field of public administration by focusing on its structural components and theories. It would also introduce students to the principles and constraints that form the environment of the public administrator. Students would learn the different concepts and major topics of public administration and its intellectual development. Students will get acquainted with the structure, issues and "themes" of the public service especially in Malaysia